2018
DOI: 10.1002/cphc.201701202
|View full text |Cite
|
Sign up to set email alerts
|

A Kinetic Study of Methane Partial Oxidation over Fe‐ZSM‐5 Using N2O as an Oxidant

Abstract: Catalytic methane oxidation using N O was investigated at 300 °C over Fe-ZSM-5. This reaction rapidly produces coke (retained organic species), and causes catalyst fouling. The introduction of water into the feed-stream resulted in a significant decrease in the coke selectivity and an increase in the selectivity to the desired product, methanol, from ca. 1 % up to 16 %. A detailed investigation was carried out to determine the fundamental effect of water on the reaction pathway and catalyst stability. The delp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 55 publications
(133 reference statements)
0
22
0
Order By: Relevance
“…Comparatively, ZnO nanorods under the same conditions show poor rate in the photocatalytic oxidation of methane. The difference in their photocatalytic activities may arise from the difference in the number of active sites in light of having comparable surface areas. Thermodynamically, polar facets on account of high energy are much reactive than nonpolar facets and as such may induce polarity in a stable and highly symmetrical molecule like methane. , …”
Section: Resultsmentioning
confidence: 99%
“…Comparatively, ZnO nanorods under the same conditions show poor rate in the photocatalytic oxidation of methane. The difference in their photocatalytic activities may arise from the difference in the number of active sites in light of having comparable surface areas. Thermodynamically, polar facets on account of high energy are much reactive than nonpolar facets and as such may induce polarity in a stable and highly symmetrical molecule like methane. , …”
Section: Resultsmentioning
confidence: 99%
“…73 For the first time, Narsimhan et al 72 reported the direct catalytic methane oxidation with oxygen or water at a reaction temperature of 210 C. The effect of water stream on the direct methane oxidation over Fe-ZSM-5 was investigated using N 2 O as oxidant. 74 Interestingly, the introduction of stream enhanced the desired product selectivity of methanol from 1% to 16% and inhibited coke formation. The presence of water in the reaction environment favors methanol desorption and inhibits coke formation via the competitive adsorption of water.…”
Section: Oxides and Fe-or Cu-based Zeolitesmentioning
confidence: 99%
“…Here, 0.4 wt% Fe–ZSM-5 (23) was identified as a suitable catalyst formulation for acid washing, due to the presence of extra-framework ɑ-Fe species and minor levels of spectator Fe x O y nano-particulates and clusters. Previous work within the group has shown that it is difficult to distinguish between the Fe species present at higher weight loadings, therefore lower weight loadings were selected for acid washing to enable changes to be noted [82, 83]. After acid washing the calcined catalyst, ICP-OES analysis of the digested samples revealed that the weight loading had reduced to 0.16%.…”
Section: Resultsmentioning
confidence: 99%